The Myth of Sonom, the Hmong King - Robert Entenmann (Hmong Studies Journal, 2005)
This paper discusses the inaccurate designation of Sonom, an important figure in 18th century Chinese history as a Hmong king. The myth of Sonom as a Hmong historical figure has gained currency through its inclusion in several widely read written works related to Hmong-Americans published over the past decade. The article clarifies the actual historical identity of Sonom and the likely route by which he became misidentified by some writers as being of Hmong origin.